PAYROLL INFORMATION SYSTEM IN CV. SASTRA TJITRA GRAFIKA USING MICROSOFT ACCESS 2000 - Husni Mubarak; Marzuki, Skom, MMSI Marzuki, Skom, MMSI (Jurnal Sistem Informasi, 2005)
In this era of globalization in the field of information today, use of computer technology in the sense of very important and becomes an absolute necessity to support various aspects of life both business, social, economic and in social life. The development of computer technology is becoming more and more rapidly developing both in hardware and software where it is intended to help facilitate the work of man.Like the CV. Sastra Tjitra Graphic uses a very manual process in the processing of payment transactions. To the writer tries to create a system design Microsoft Access 2000 is expected to help simplify the daily work and in preparing reports on the place.